2002
DOI: 10.1038/sj.ejhg.5200828
|View full text |Cite
|
Sign up to set email alerts
|

Thirty distinct CACNA1F mutations in 33 families with incomplete type of XLCSNB and Cacna1f expression profiling in mouse retina

Abstract: X-linked CSNB patients may exhibit myopia, nystagmus, strabismus and ERG abnormalities of the Schubert-Bornschein type. We recently identified the retina-specific L-type calcium channel a1 subunit gene CACNA1F localised to the Xp11.23 region, which is mutated in families showing the incomplete type (CSNB2). Here, we report comprehensive mutation analyses in the 48 CACNA1F exons in 36 families, most of them from Germany. All families were initially diagnosed as having the incomplete type of CSNB, except for two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…However, most of the CSNB cases described so far are associated with mutations in the two X-linked genes CACNA1F and NYX [Bech-Hansen et al, 1998Strom et al, 1998;Pusch et al, 2000;Nakamura et al, 2001;Boycott et al, 2001;Wutz et al, 2002;Zito et al, 2003;Allen et al, 2003;Jacobi et al, 2003;Zeitz et al, 2005a]. Recently, we and others showed that mutations in the GRM6 gene (MIM] 604096), encoding the human mGluR6, lead to autosomal recessive congenital stationary night blindness (arCSNB) [Dryja et al, 2005;Zeitz et al, 2005b].…”
Section: Introductionmentioning
confidence: 96%
“…However, most of the CSNB cases described so far are associated with mutations in the two X-linked genes CACNA1F and NYX [Bech-Hansen et al, 1998Strom et al, 1998;Pusch et al, 2000;Nakamura et al, 2001;Boycott et al, 2001;Wutz et al, 2002;Zito et al, 2003;Allen et al, 2003;Jacobi et al, 2003;Zeitz et al, 2005a]. Recently, we and others showed that mutations in the GRM6 gene (MIM] 604096), encoding the human mGluR6, lead to autosomal recessive congenital stationary night blindness (arCSNB) [Dryja et al, 2005;Zeitz et al, 2005b].…”
Section: Introductionmentioning
confidence: 96%
“…The incomplete form, CSNB2, is caused by mutations in the Cacna1f gene, encoding the α 1F subunit of VDCCs (Bech-Hansen et al, 1998;Strom et al, 1998;Boycott et al, 2001;Wutz et al, 2002). In the outer retina, expression of the α 1F subunit has been localized to the OPL where it is concentrated on the presynaptic side in the terminals of the photoreceptors at their "active zones," which are specialized to mediate continuous calcium-dependent neurotransmitter release (Morgans et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, inactivation of CACNA1F, the gene encoding Ca v 1.4 (Ca v 1.4 KO), disrupts photoreceptor synaptic transmission and presynaptic calcium signaling (15) and prevents the maturation of photoreceptor synapses (13,16). In addition, human mutations in CACNA1F cause vision disorders, including incomplete congenital stationary night blindness 2, which is characterized by impaired rod photoreceptor transmission and low visual acuity in darkness (17)(18)(19)(20). Antibody labeling for the Ca v 1.3 ␣ 1 subunit has also been detected in the cones from tree shrew (21,22) and chick (23).…”
Section: Camentioning
confidence: 99%